Evaluasi Dan Perbaikan Proses Bisnis Pengelolaan Siswa Menggunakan Business Process Improvement (Studi Pada: Lingua Institute) - Devita Widyasari; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Lingua Institute is a course institution that provides foreign language education and training. Student Management is the main service carried out by cross-functional divisions at Lingua Institute. This service focuses on student data as an object and includes matters relating to collecting, processing, storing, and distributing student data information. But Lingua Institute still has problems when running its business processes, such as the absence of rules and standard business process flow, therefore business processes run less effectively and efficiently; data recording and data storing are still manual so it is vulnerable to data loss; and delays in making learning modules. Therefore, analysis, evaluation and improvement of business processes are needed to solve these problems and to maximize the running of business processes. In this study, business processes are modeled using Business Process Modeling and Notation (BPMN), then analyzed and evaluated using the Failure Mode and Effect Analysis (FMEA) and Five Whys Analysis and finally improved by Business Process Improvement (BPI) method. Afterward, the current business process model and recommended business process model are simulated to validate and to indicate the time efficiency of the recommended business process. In a simulation of one business process, it is found that each activity is valid and there is a time reduction of 1 hour 2 minutes 16 seconds or an increase in time efficiency of 13.93%. This happens because of improvements such as changing some activities and utilizing Information System.